Cardiac hyporesponsiveness in severe sepsis is associated with nitric oxide-dependent activation of G protein receptor kinase - Dal-Secco, Daniela; DalBo, Silvia; Lautherbach, Natalia E. S.; Gava, Fabio N.; Celes, Mara R. N.; Benedet, Patricia O.; Souza, Adriana H.; Akinaga, Juliana [UNESP]; Lima, Vanessa [UNESP]; Silva, Katiussia P. [UNESP]; Kiguti, Luiz Ricardo A. [UNESP]; Rossi, Marcos A.; et al. (Amer Physiological Soc, 2017)
G protein-coupled receptor kinase isoform 2 (GRK2) has a critical role in physiological and pharmacological responses to endogenous and exogenous substances. Sepsis causes an important cardiovascular dysfunction in which nitric oxide (NO) has a relevant role. The present study aimed to assess the putative effect of inducible NO synthase (NOS2)-derived NO on the activity of GRK2 in the context of septic cardiac dysfunction. C57BL/6 mice were submitted to severe septic injury by cecal ligation and puncture (CLP). Heart function was assessed by isolated and perfused heart, echocardiography, and beta-adrenergic receptor binding. GRK2 was determined by immunofluorescence and Western blot analysis in the heart and isolated cardiac myocytes. Sepsis increased NOS2 expression in the heart, increased plasma nitrite + nitrate levels, and reduced isoproterenol-induced isolated ventricle contraction, whole heart tension development, and beta-adrenergic receptor density. Treatment with 1400W or with GRK2 inhibitor prevented CLP-induced cardiac hyporesponsiveness 12 and 24 h after CLP. Increased labeling of total and phosphorylated GRK2 was detected in hearts after CLP. With treatment of 1400W or in hearts taken from septic NOS2 knockout mice, the activation of GRK2 was reduced. 1400W or GRK2 inhibitor reduced mortality, improved echocardiographic cardiac parameters, and prevented organ damage. Therefore, during sepsis, NOS2-derived NO increases GRK2, which leads to a reduction in beta-adrenergic receptor density, contributing to the heart dysfunction. Isolated cardiac myocyte data indicate that NO acts through the soluble guanylyl cyclase/cGMP/PKG pathway. GRK2 inhibition may be a potential therapeutic target in sepsis-induced cardiac dysfunction. NEW & NOTEWORTHY The main novelty presented here is to show that septic shock induces cardiac hyporesponsiveness to isoproterenol by a mechanism dependent on nitric oxide and mediated by G protein-coupled receptor kinase isoform 2. Therefore, G protein-coupled receptor kinase isoform 2 inhibition may be a potential therapeutic target in sepsis-induced cardiac dysfunction.
Keywords: beta-adrenergic receptors; G protein receptor kinase; inducible nitric oxide synthase; nitric oxide; sepsis